Dinamika Pencapaian Identitas Sosial Positif Atas Keistimewaan Yogyakarta - Muhammad Johan Nasrul Huda (UIN Sunan Kalijaga, 2014)
Artikel ini bertujuan untuk memahami secara mendalam dinamika kelompok pro penetapan dalam memaknai dan mencapai identitas sosial positif atas status keistimewaan Yogyakarta. Penelitian ini menggunakan pendekatan fenomenologi dengan jumlah subyek 6 orang yang merupakan anggota kelompok pro-penetapan. Hasil penelitian menggambarkan bahwa kelompok pro penetapan mempersepsikan bahwa demokrasi bukan didefinisikan secara tunggal, tetapi disesuaikan dengan lokalitas budaya masyarakatnya. Pemaknaan terhadap keistimewaan Yogyakarta meliputi unsur penetapan pemimpin secara langsung, pengelolaan pertanahan, tata ruang, kelembagaan pemerintahan dan kebudayaan sesuai tradisi yang sudah berjalan ratusan tahun lalu. Kelompok pro penetapan menggunakan strategi kompetisi sosial dalam mencapai/mempertahankan identitas sosial positif atas status keistimewaan Yogyakarta.This article tries to focus deeper on the dynamic of pro-stipulation group in identifying meaning which given on Yogyakarta’s province as special status. As part of identity it follows with their strategy to achieve positive social identity. The research used both qualitative method and phenomenological framework. Subject consist of six (6) individuals, stand from member of pro-authority group. The result is that meaning of Yogyakarta’s special status relate with democracy, for the people of Yogyakarta it was not singular definition like in modern concept already given the meaning toward it. Furthermore, there are meanings of Yogyakarta’ special status include stipulation leader, authority in landform, public space, administration of government and cultural identity that has been rooted for hundreds of years ago. Last part of this research is the finding of cultural competition as an effective strategy of to achieve positive social identity. It is so, since the action implicates the obvious gap between local and national identity throughout the strategy. Key words : social identity, redefinition of democracy, social competition